Pengaruh Disiplin Kerja, Insentif, Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Hotel Mataram - Supratman; Tama Krisnahadi; Shabrina Dwi Regita (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to determine the effect of work discipline, incentives, and work motivation on employee performance at the Mataram Hotel. This study is included in quantitative research with an associative strategy. The population of this study was all employees of the Mataram Hotel in 2024 with a sample of 17 employees. The data that has been taken through the questionnaire is proven to be valid and reliable. The results of the study indicate that: 1) There is no effect of work discipline on employee performance because the ; 2) There is no effect of incentives on employee performance because the ; 3) There is an effect of work motivation on employee performance because the ; and 4) There is a significant joint effect between work discipline, incentives, and work motivation on employee performance with a contribution of and is influenced by other variables not studied.